A Comprehensive Review on Recently Detected Herbal Phytoactives Having Anti-Diabetic Potential for Various Diabetes-Related Complications - Wal, Pranay; Wal, Ankita; Pal, Rashmi S.; Singh, Priya (Current Traditional Medicine, 2021)
Background: Diabetes is a metabolic, endocrine disorder that is featured by hyperglycemia and glucose intolerance, primarily due to beta cell destruction, with insulin resistance playing a secondary role. It is treated with the help of many chemical-based drugs as well as natural derivatives. Objective: There is an urgent need to develop new efficacious, cheaper and more available drugs to face this growing public health challenge. Many anti-diabetic drugs are often associated with many adverse effects. Materials & Methods: Literature was reviewed in a narrative manner in order to obtain information regarding active phytoactives present in different plants. Anti-diabetic drugs are often loaded with side effects; therefore, this review was carried out for the selection of effective natural therapeutic moieties with less or no adverse effects. Results: In this review article, we have described the details of recently detected bioactive compounds present in different natural substances which can be used effectively for diabetes-related adversities. Conclusion: Natural products-based bioactive molecules have been proven to improve insulin resistance and other related complications through suppression of inflammatory signaling pathways.
Keywords: insulin